Client Perceptions of an FASD-Informed Indigenous Restorative Justice Program - Flannigan, Katherine; Rollans, Benjamin; Tremblay, Melissa; Potts, Sandra; O'Riordan, Teresa; Rasmussen, Carmen; Pei, Jacqueline (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Individuals with fetal alcohol spectrum disorder (FASD) can experience multiple layers of adversity that increase vulnerability to justice involvement. Given the systemic overrepresentation of Indigenous Peoples in the justice system, community-based interventions are important for supporting Indigenous individuals with FASD who are justice-involved, yet little is known about individual experiences with such interventions. In this community-based study, we conducted interviews with 12 adults in an FASD-informed Indigenous justice program, revealing stories of coping, growth, and hope. Findings suggest that blending FASD assessment with restorative justice approaches can contribute to physical, human, family/social, and community/cultural resources that support wellbeing. We describe tangible strengths and processes to leverage in practice and policy for supporting justice-involved individuals with FASD across settings and communities.